(untitled) (Research, Society and Development, 2020)
An alternative for the control verminosis in sheep is the use of bioactive plants. Several studies have related tanniferous plants with anthelmintic properties, especially banana (Musa spp.). Therefore, the objective of this work was to qualify and quantify the anthelmintic potential of the hydroalcoholic extract of the 10% banana floral bud (HEB), in the concentrations of 20, 40, 80, 160 and 320mg mL-1, on eggs and larvae of gastrointestinal nematodes of sheep. The present laboratory study, quantitative in nature, is justified mainly by the fact that in vitro studies are required preliminarily to pre-clinical and clinical trials. Thus, feces from naturally infected sheep were used, selected by the minimum count of 2,000 eggs per gram of feces and in quadruplicate, negative and positive control treatments were also evaluated. In addition, the contents of total polyphenols, condensed tannins, flavonoids, and antioxidant activity were determined. Using the eggs hatchability inhibition tests (EHT) and larval migration (LMIT), it was possible to verify 100% inhibition, for both tests, in the concentration of 320mg mL-1. HEB (10mg mL-1) showed 0.38mg EAG g-1 of total polyphenols, 372.70mg EAT g-1 of tannins, 0.42mg RE g-1 of flavonoids, and antioxidant activity of 43, 03% with IC50 corresponding to 0.2765mg mL-1. In this way, it was possible to verify the anthelmintic and antioxidant activity of HEB, demonstrating an important potential in controlling worms in sheep.